Prevention and Treatment Strategies for Alzheimer’s Disease: Focusing on Microglia and Astrocytes in Neuroinflammation - Zhang S; Gao Z; Feng L; Li M (Dove Medical Press, 2024)
Shenghao Zhang,1,* Zhejianyi Gao,2,* Lina Feng,1,3 Mingquan Li1 1Department of Neurology, The Third Affiliated Hospital of Changchun University of Chinese Medicine, Changchun, Jilin Province, 130021, People's Republic of China; 2Department of Orthopaedics, Fushun Hospital of Chinese Medicine, Fushun, Liaoning Province, 113008, People's Republic of China; 3Shandong Key Laboratory of TCM Multi-Targets Intervention and Disease Control, The Second Affiliated Hospital of Shandong First Medical University, Taian, Shandong Province, 271000, People's Republic of China*These authors contributed equally to this workCorrespondence: Lina Feng; Mingquan Li, Department of Neurology, the Third Affiliated Hospital of Changchun University of Chinese Medicine, Changchun, Jilin, 130117, People's Republic of China, Tel +86-15543120222 ; +86-15948000577, Email Fenglina0001@163.com; Limingquan0001@126.comAbstract: Alzheimer's disease (AD) is a fatal neurodegenerative disease characterized by its insidious onset and progressive development, making it the most common form of dementia. Despite its prevalence, the exact causes and mechanisms responsible for AD remain unclear. Recent studies have highlighted that inflammation in the central nervous system (CNS) plays a crucial role in both the initiation and progression of AD. Neuroinflammation, an immune response within the CNS triggered by glial cells in response to various stimuli, such as nerve injury, infection, toxins, or autoimmune reactions, has emerged as a significant factor alongside amyloid deposition and neurofibrillary tangles (NFTs) commonly associated with AD. This article aims to provide an overview of the most recent research regarding the involvement of neuroinflammation in AD, with a particular focus on elucidating the specific mechanisms involving microglia and astrocytes. By exploring these intricate processes, a new theoretical framework can be established to further probe the impact of neuroinflammation on the development and progression of AD. Through a deeper understanding of these underlying mechanisms, potential targets for therapeutic interventions and novel treatment strategies can be identified in the ongoing battle against AD.Keywords: alzheimer's disease, neuroinflammation, microglia, astrocyte, review